2016
DOI: 10.1021/acs.jpcb.5b11716
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Percolation in Semiconducting Binary Polymer Nanoparticle Glasses

Abstract: Binary polymer nanoparticle glasses provide opportunities to realize the facile assembly of disparate components, with control over nanoscale and mesoscale domains, for the development of functional materials. This work demonstrates that tunable electrical percolation can be achieved through semiconducting/insulating polymer nanoparticle glasses by varying the relative percentages of equal-sized nanoparticle constituents of the binary assembly. Using time-of-flight charge carrier mobility measurements and cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…data is R 2 = 0.98, yielding as fitting parameters a = 0.16, p c = 18%, and t = 2.9. We have previously shown that conducting/insulating polymer nanoparticle assemblies follow predictions of the classical lattice‐model percolation theory . However, the power‐law parameters in MIEC systems yield parameters that deviate from lattice‐model percolation theory predictions.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…data is R 2 = 0.98, yielding as fitting parameters a = 0.16, p c = 18%, and t = 2.9. We have previously shown that conducting/insulating polymer nanoparticle assemblies follow predictions of the classical lattice‐model percolation theory . However, the power‐law parameters in MIEC systems yield parameters that deviate from lattice‐model percolation theory predictions.…”
Section: Resultsmentioning
confidence: 92%
“…Based on recent studies in MIECs, we used poly(3‐hexylthiophene) (P3HT, Rieke Metals, M̅ W = 36 kDa, regioregularity = 96%, and polydispersity Đ = 2.3) nanoparticles for electronic conduction . We chose to study Li‐ion transport because of its relevance in energy storage applications.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations